Mutation detection in the human HSP70B′ gene by denaturing high-performance liquid chromatography - Hecker, Karl H. (Cell Stress Society International, 2000)
Variances, particularly single nucleotide polymorphisms (SNP), in the genomic sequence of individuals are the primary key to understanding gene function as it relates to differences in the susceptibility to disease, environmental influences, and therapy. In this report, the HSP70B′ gene is the target sequence for mutation detection in biopsy samples from human prostate cancer patients undergoing combined hyperthermia and radiation therapy at the Dana-Farber Cancer Institute, using temperature-modulated heteroduplex analysis (TMHA). The underlying principles of TMHA for mutation detection using DHPLC technology are discussed. The procedures involved in amplicon design for mutation analysis by DHPLC are detailed. The melting behavior of the complete coding sequence of the target gene is characterized using WAVEMAKER(TM) software. Four overlapping amplicons, which span the complete coding region of the HSP70B′ gene, amenable to mutation detection by DHPLC were identified based on the software-predicted melting profile of the target sequence. TMHA was performed on PCR products of individual amplicons of the HSP70B′ gene on the WAVE® Nucleic Acid Fragment Analysis System. The criteria for mutation calling by comparing wild-type and mutant chromatographic patterns are discussed.